Positive predictive factors for urogenital injuries in severely injured patients with pelvic and spinal fractures: introducing the UPPS scoring system - Bohe, Olivia Anna; Wenk, Maren; Brunnemer, Suna; Faymonville, Christoph; Honeck, Patrick; Horn, Thomas; Biberthaler, Peter; Hanschen, Marc (Medicina, 2022)
Background and Objectives: Although urogenital injuries are common in severely injured patients, their diagnosis is often delayed. Predicting genitourinary injuries (GUI), especially in the immediate stages post injury, remains a challenge. This study aims to evaluate and determine positive predictive factors for the presence of GUI in polytrauma patients. Subsequently, these factors shall be used to develop an easy-to-use scoring system, deployable directly in the emergency setting. Materials and Methods: This study evaluates all severely injured patients with an Injury Severity Score (ISS) ≥ 16 admitted to the emergency departments of two German university hospitals between 2016 and 2020. These patients were retrospectively scanned for injuries of the thoracic and/or lumbar spine and/or the pelvic girdle. Demographic data was analyzed alongside trauma mechanism, type of injuries, mortality, length of hospital stays, surgeries, laboratory results, and urological treatment. Subgroup analysis was performed to compare patients with and without GUIs using t-tests. Conducting a binary logistic regression model, the significant factors were combined to create a scoring system, which was further analyzed for accuracy. Results: In total, 413 patients with an average ISS of 33.8 ± 15.0 were identified, and 47 patients (11.4%) sustained urogenital injuries with an average Abbreviated Injury Scale (AIS) score of 2.3 ± 1.1 (range: 1-5). The severity of the pelvic girdle injury correlated with the presence of urogenital injuries (p = 0.002), while there was no correlation with spinal injuries. Moreover, most GUIs resulted from motorcycle accidents (p < 0.001) and 87.2% of these patients were male. Patients with GUI were significantly more likely to show macrohematuria (p < 0.001) on admission and were more severely injured overall (ISS > 34). There was no significant difference in the length of intensive care unit (ICU) stay, the days until discharge, or death rates. Conclusions: Factors or circumstances which reliably predict the presence of GUI were found to include the male sex, a motorcycle accident, high severity of pelvic girdle fractures, macrohematuria on admission to the emergency department, and an ISS > 34. With these findings, we introduce the ‘Urotrauma in Polytrauma patients with Pelvic and/or Spinal injuries’ (UPPS) score for easier prediction of GUI in the emergency setting.